Enhanced sensitization to animal, interpersonal, and intergroup fear‐relevant stimuli (but no evidence for selective one‐trial fear learning). (18th August 2015) - Lipp, Ottmar V.; Cronin, Sophie L.; Alhadad, Sakinah S. J.; Luck, Camilla C.
Abstract Selective sensitization has been proposed as an alternative explanation for enhanced responding to animal fear‐relevant stimuli—snakes and spiders—during extinction of Pavlovian fear conditioning. The current study sought to replicate the phenomenon using a shock workup procedure as the sensitizing manipulation and to extend it to interpersonal and intergroup fear‐relevant stimuli—angry faces and other‐race faces. Assessment of selective sensitization was followed by a one‐trial fear learning procedure. Selective sensitization, larger electrodermal responses to fear‐relevant than to control stimuli after sensitization, or a larger increase in electrodermal responding to fear‐relevant than to control stimuli after sensitization was observed across stimulus domains. However, the one‐trial fear learning procedure failed to provide evidence for enhanced fear conditioning to fear‐relevant stimuli. One‐trial fear learning was either absent or present for fear‐relevant and nonfear‐relevant stimuli. The current study confirms that electrodermal responses to fear‐relevant stimuli across stimulus domains are subject to selective sensitization.